Light Fertilization Affects Growth and Photosynthesis in Mung Bean (Vigna radiata) Plants - Amitrano, Chiara; Vitale, Ermenegilda; Micco, Veronica De; Arena, Carmen (Journal of Environmental Accounting and Management, 2026)
In a climate change scenario, the optimization of growth conditions for food crop species plays a key role for the sustainability of cultivation. Agrotechnologies need to be improved to set up the best conditions to maximize plant development, production and resource use efficiency in growth chambers and greenhouses. The manipulation of light quality during plant growth may be used as a powerful mean to obtain specific functional traits. This practice may be useful to improve plant growth, also avoiding the use of large doses of chemical fertilizers, which may compromise the environment and human health. In our study, we analyzed specific physiological traits of mung bean (Vigna radiata) seed-lings grown at different light quality regimes (W-White, R-Red and RB-Red-Blue ight), to assess the best light treatment in promoting plant development and photosynthesis. Plant growth was monitored measuring stem and root elongation, dry biomass and total leaf area. The integrity of the photosynthetic machinery was monitored through fluorescence an emission measurements and content of photosynthetic pigments and total proteins. Our results showed that he growth under R wavelengths promoted stem elongation compared to W and RB. This light treatmentwas also responsible for the highest production of total chlorophylls. Photochemistry was not affected by the different light qualities. RB light induced a compact architecture of plants and the highest amount of proteins. Overall results indicate that different light quality regimes can be applied during the cultivation to consciously modify plant growth and development. Thus, it will be fundamental to optimize and choose opportunely not only the intensity but also the spectral composition of light to maximize the productivity of a specific crop in quantitative and qualitative terms.